Ryanair: matching the activity system to the strategy - Grant, Robert (Henry Stewart Talks, 2017)
This case study describes Ryanair’s activity system and the company’s key success factor: low fares enabled by low operating costs. The case study shows that Ryanair succeeds by closely matching all of its activities to its strategy of maintaining low operating costs.